Semaphorin3A: A Potential Therapeutic Tool for Lupus Nephritis - Bejar, Jacob; Kessler, Ofra; Sabag, Adi D.; Sabo, Edmond; Itzhak, Ofer Ben; Neufeld, Gera; Vadasz, Zahava (Frontiers in Immunology, 2018)
Background: The immune regulatory properties of semaphorin3A (sema3A) (both innate and adaptive) are well established in many in-vitro studies. The injection of sema3A into a mice model of rheumatoid arthritis was proven to be highly beneficial, both in attenuating clinical symptoms and in decreasing inflammatory mechanisms. Objectives: This study was designed in order to assess the possible therapeutic benefits of sema3A following its injection into female NZB/W mice. Methods: Forty-eight NZB/W mice were recruited for this study. Thirty mice were treated as a "prevention group" and 18 were used as a "treatment group." Eight- week-old mice were acclimated and then divided into the two above-mentioned groups. Results: The injection of sema3A into young mice (at week 12) before the onset of disease (the prevention group), delayed the appearance of proteinuria. Here, the median time to severe proteinuria was 110 days, 95% CI: 88 -131. However, in mice in which the empty vector was injected, the median time to severe proteinuria was 63 days, 95% CI: 0-139. Sema3A treatment, significantly reduced renal damage, namely, it prevented the deposition of immune complexes in the glomeruli. When sema3A was injected at the onset of proteinuria (the treatment group), aiming to treat rather than to prevent disease in these mice, survival was increased and the deterioration of proteinuria was delayed. Conclusion: Semaphorin3A is highly beneficial in reducing lupus nephritis in NZB/W mice. It delays the appearance and deterioration of proteinuria, and increases the survival rates in these mice. The regulatory mechanisms of sema3A involve both innate and adaptive immune responses. Further studies will establish the idea of applying sema3A in the treatment of lupus nephritis.